2019
DOI: 10.3390/ma12162547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zn and Sn on the Precipitation Behavior of New Al–Mg–Si Alloys

Abstract: In this study, we demonstrate how Zn and Sn influence hardening behavior and cluster formation during pre-aging and paint bake treatment in Al–Mg–Si alloys via hardness tests, tensile tests, and atom probe tomography. Compared to the standard alloy, the Sn-modified variant shows reduced cluster size and yield strength in the pre-aged condition. During the paint bake cycle, the clusters start to grow very fast and the alloy exhibits the highest strength increment. This behavior is attributed to the high vacancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Sn introduction slows down the natural ageing process of 6000 Al alloys, thus helping in keeping the alloy stable during the transportation period from one place to another [5]. It was also observed that Zinc addition eliminates the negative effect of Sn addition in the properties of high magnesium content 6000 Al alloy [6]. Sn addition in 6000 alloys had been also shown as a potential accelerating artificial age hardening agent [7][8][9].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Sn introduction slows down the natural ageing process of 6000 Al alloys, thus helping in keeping the alloy stable during the transportation period from one place to another [5]. It was also observed that Zinc addition eliminates the negative effect of Sn addition in the properties of high magnesium content 6000 Al alloy [6]. Sn addition in 6000 alloys had been also shown as a potential accelerating artificial age hardening agent [7][8][9].…”
Section: Introductionmentioning
confidence: 95%
“…Alloying elements like Mg and Si in 6000 alloys reduce the dislocation motion through formation of hardening Mg 2 Si precipitates, thereby increasing the mechanical strength [4]. Sn in 6000 Al alloys is a potential trace element [5][6][7][8][9][10]. Sn introduction slows down the natural ageing process of 6000 Al alloys, thus helping in keeping the alloy stable during the transportation period from one place to another [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 The effect of alloying Sn on the mechanical properties of the Al-Mg-Si alloy very much depends on the Mg/Si ratio and the ageing temperature. [13][14][15][16][17][18] At pre-aged (110 °C) and paint bake (165 °C) conditions, the negative effect of Sn (0.04 wt%) on the mechanical properties in high Mg-rich Al-Mg-Si alloy (Mg/Si = * 2) was observed by Glockel et al 14 However, the simultaneous addition of Zn (3 wt%) and Sn was found to prevent the negative effect and significantly improve the mechanical properties of the alloy. This was because Sn suppresses Mg-Si co-cluster formation, whereas Zn promotes Mg-Si co-cluster formation.…”
Section: Introductionmentioning
confidence: 98%
“…Many researches illustrated that the CuO nano-composite demands ganglion manner, which includes altitude degree; an extended interval. CuO is synthesized using high reaction (at 673 K for 720 min using 15% argon and 85% O 2 atmosphere); the Cu at first is created using a radio frequency (RF) sputtering apparatus [15,16].…”
Section: Introductionmentioning
confidence: 99%